2022
DOI: 10.1186/s12886-021-02178-w
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative measurements of choroidal thickness and volume in diabetic retinopathy using optical coherence tomography and optical coherence tomography angiography; correlation with vision and foveal avascular zone

Abstract: Background To represent choroidal thickness (CT) and choroidal volume (CV) databases in diabetic retinopathy (DR) patients and healthy control participants using optical coherence tomography (OCT) and enhanced depth imaging OCT (EDI-OCT). No study had evaluated CT at all main stages of diabetic retinopathy in a single study. Methods The study included 176 eyes from 93 patients (39–80 years old; 42% females) who were divided into three groups based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…In another study, SCT examination using EDI-OCT and foveal avascular zone using OCTA. Although the results of the study did not find a correlation between SCT and the foveal avascular zone, this study has shown a new method to determine the association of SCT changes in patients with type 2 DM 21.…”
contrasting
confidence: 63%
“…In another study, SCT examination using EDI-OCT and foveal avascular zone using OCTA. Although the results of the study did not find a correlation between SCT and the foveal avascular zone, this study has shown a new method to determine the association of SCT changes in patients with type 2 DM 21.…”
contrasting
confidence: 63%
“…CT is used as a surrogate biomarker for the evaluation of choroidal vascularization, but it cannot indicate the affected choroidal component [ 50 ]. Agrawal et al defined the ratio between LA and TCA as CVI [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OCT-A can be utilized for conditions involving vascular damage or choroidal neovascularization (CNV) (25). Apart from allowing the subjective identification of vascular abnormalities, OCT-A can also provide quantitative data (vessel density, blood flow, and foveal avascular zone size) that could be employed as vascular biomarkers (27)(28)(29)(30)(31)(32).…”
Section: Optical Coherence Tomography Angiographymentioning
confidence: 99%